Interpretation of the Spirit of the Era and Personality in Temurpolat Tillaev's Work (Based on the Story "O‘Lim O‘pqoni") (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2023)
This article analyzes the spirit of the era and the problem of personal interpretation in the story "O‘lim o‘pqoni" by the great representative of Uzbek literature, Temurpolat Tillaev, whose works have passed the test of 30 years of time, and which was created before independence entering the series of truthfully reflected works, at the same time, the writer has been creating effectively and has written a number of works, and in this story, the spirit of the era, symbolic expressions through the image of Turan, and at the same time, it was not easy to achieve independence during the story, in this way, what is our nation It is important because it analyzes the issue of bloodshed and reflects the truth related to the appreciation of today's bright days.